Expression and membrane-targeting of an active plant cytochrome P450 in the chloroplast of the green alga Chlamydomonas reinhardtii. (February 2015) - Gangl, Doris; Zedler, Julie A.Z.; Włodarczyk, Artur; Jensen, Poul Erik; Purton, Saul; Robinson, Colin
Abstract : Graphical abstract: A cytochrome P450 has been expressed in Chlamydomonas chloroplasts and targeted into the membranes in an active form. Highlights: We expressed a plant cytochrome P450 in the Chlamydomonas reinhardtii chloroplast. A novel chloroplast transformation was used. The enzyme is efficiently targeted to membranes. The P450 is active. The results imply that P450-based processes can be reproduced in the chloroplast. Abstract: The unicellular green alga Chlamydomonas reinhardtii has potential as a cell factory for the production of recombinant proteins and other compounds, but mainstream adoption has been hindered by a scarcity of genetic tools and a need to identify products that can be generated in a cost-effective manner. A promising strategy is to use algal chloroplasts as a site for synthesis of high value bioactive compounds such as diterpenoids since these are derived from metabolic building blocks that occur naturally within the organelle. However, synthesis of these complex plant metabolites requires the introduction of membrane-associated enzymes including cytochrome P450 enzymes (P450s). Here, we show that a gene ( CYP79A1 ) encoding a model P450 can be introduced into the C. reinhardtii chloroplast genome using a simple transformation system. The gene is stably expressed and the P450 is efficiently targeted into chloroplast membranes by means of its endogenous N-terminal anchor domain, where it is active and accounts for 0.4% of total cell protein. These results provide proof of concept for the introduction of diterpenoid synthesis pathways into the chloroplast of C. reinhardtii .